Abortion as agentive action: reproductive agency among young women seeking post-abortion care in Uganda. - Cleeve, Amanda; Faxelid, Elisabeth; Nalwadda, Gorette; Klingberg-Allvin, Marie (An International Journal for Research, Intervention and Care, 2017)
Unsafe abortion in Africa continues to be a major contributor to the global maternal mortality which affects young women in particular. In Uganda, where abortion is legally restricted and stigmatised, unsafe abortion is a major public health issue. We explored reproductive agency in relation to unsafe abortion among young women seeking post-abortion care. Through in-depth interviews we found that reproductive agency was constrained by gender norms and power imbalances and strongly influenced by stigma. Lack of resources and the need for secrecy resulted in harmful abortion practices and delayed care-seeking. Women did not claim ownership of the abortion decision, but the underlying meaning in the narratives positioned abortion as an agentive action aiming to regain control over one's body and future. Women's experiences shaped contraceptive intentions and discourse, creating a window of opportunity that was often missed. This study provides unique insight into how young women negotiate and enact reproductive agency in Uganda. Health systems need to strengthen their efforts to meet young women's sexual and reproductive health needs and protect their rights. Enabling young women's agency through access to safe abortion and contraception is paramount.
Keywords: Gender norms; Uganda; reproductive agency; unsafe abortion; young women